1968
DOI: 10.1002/cpt196895598
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dosage form on the activity of a diuretic agent

Abstract: Tablets and capsules of a combination product containing triamterene and hydrochlorothiazide in a 2:1 ratio were compared in a series of short‐term studies with male volunteers. The tablet caused approximately twice as much excretion of hydrochlorothiazide and 3 times as much triamterene as the capsule. These studies provide further evidence of the importance of the dosage forms in the effectiveness of drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Another sulfonamide-type diuretic, hydrochlorothiazide, has shown variable dissolution characteristics for tablet formulations (6,"). Tannenbaum et al (8) showed that product formulation could affect the bioavailability of hydrochlorothiazide dosage forms, although recently (9, 10) several groups showed that possible differences in dissolution may not be reflective of significant differences in the bioavailability of commercial products. These studies were based on urinary excretion data only, however.…”
mentioning
confidence: 99%
“…Another sulfonamide-type diuretic, hydrochlorothiazide, has shown variable dissolution characteristics for tablet formulations (6,"). Tannenbaum et al (8) showed that product formulation could affect the bioavailability of hydrochlorothiazide dosage forms, although recently (9, 10) several groups showed that possible differences in dissolution may not be reflective of significant differences in the bioavailability of commercial products. These studies were based on urinary excretion data only, however.…”
mentioning
confidence: 99%
“…Such differences have been reported for some drugs, e.g. chlorothiazide and triamterine (Tannenbaum, Rosen, Flanagan & Crosley, 1968). The data implies therefore that the formulations should be therapeutically equivalent.…”
Section: Discussionmentioning
confidence: 50%
“…For metoprolol alone these properties have been extensively studied in recent years (Regirdh, Borg, Johansson, Johnsson & Palmer, 1974;Johnsson, Regardh & Solvell, 1975;Regardh, Johnsson, Jordo & Solveli, 1975) and as regards HCT there are several reports on the bioavailability of various products (Tannenbaum, Rosen & Flanagan, 1968;McGilveray, Hossie & Matlock, 1973;Wagner, Gilleran & Zak, 1975;Beermann, Groschinsky-Grind & Lindstr6m, 1977). Pharmacokinetic data of this drug were also recently reported by Beermann, Groschinsky-Grind & Rosen (1976).…”
Section: Discussionmentioning
confidence: 99%